2021
DOI: 10.1177/15344843211000260
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of Employees’ Transition to Entrepreneur: A Cognitive Mapping Approach

Abstract: Employees’ transition to an entrepreneurial career has been explained by two major driving forces: push and pull factors. The push-pull dichotomy, however, has been the center of debate on whether the classification is incomplete and ambiguous. Until this debate is resolved, the dynamic and fluid nature of the influencing factors and their relationships remains unclear. The purpose of this research is to discuss the legitimacy of the push-pull dichotomy in explaining the motivations and processes of employees’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 93 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…This argumentation has informed several studies noting that dissatisfied employees may desire to enter self-employment (Brockhaus, 1980; Cromie and Hayes, 1991; Henley, 2007), regardless of whether they experience pecuniary or nonpecuniary dissatisfaction (Guerra and Patuelli, 2016). Unsatisfactory working conditions or rewards are negative drivers forcing employees to consider an entrepreneurial path (Lee, 2021). Therefore, we propose the following:…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This argumentation has informed several studies noting that dissatisfied employees may desire to enter self-employment (Brockhaus, 1980; Cromie and Hayes, 1991; Henley, 2007), regardless of whether they experience pecuniary or nonpecuniary dissatisfaction (Guerra and Patuelli, 2016). Unsatisfactory working conditions or rewards are negative drivers forcing employees to consider an entrepreneurial path (Lee, 2021). Therefore, we propose the following:…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…These deficiencies have led to instances where some PPM studies classify a factor as push, and others classify it as pull. For example, low job satisfaction has been studied as both pushing (e.g., Nikolaev et al, 2020) as well pulling (e.g., Lee, 2021) employees into entrepreneurship.…”
Section: The Push and Pull Model Of Entrepreneurship Entrymentioning
confidence: 99%
“…Despite agreement on the frequency of transitions from wage employment to full-time entrepreneurship and the relevance of cognitions in this process, scholars contend that the field still requires “a more micro perspective of self-employment entry” (Shepherd et al, 2019, p. 166) that better explains how cognitions influence entrepreneurship entry decisions (Strike & Rerup, 2016; Wood et al, 2017). In particular, researchers (e.g., Dawson & Henley, 2012; Lee, 2021; Thébaud, 2016) have called into question the validity of the longest-standing and most popular theoretical framework used to explain employees’ career transitions to entrepreneurship: the Push and Pull Model (PPM; Amit & Muller, 1995). The PPM suggests that factors driving individuals from wage employment to entrepreneurship fall into two categories: negative factors, such as stress or stereotyping, that impel or “push” them into entrepreneurship, and positive factors, such as autonomy or job satisfaction, that draw or “pull” them in (Annink et al, 2016; Cromie, 1987; Dawson & Henley, 2012; Nikolaev et al, 2020).…”
mentioning
confidence: 99%
“…As for the basis of variable selection, entrepreneurial motivation theory points out that the formation of individual entrepreneurial behavior decisions is usually influenced by two kinds of factors: one is the factors related to an individual's current job, and the other is the factors related to entrepreneurial activities (Obschonka et al, 2015). Combining with the academic entrepreneurship, the former reflects the push effect of job-related negative factors on entrepreneurial intention, and the latter reflects the pull effect of entrepreneurshiprelated positive factors on entrepreneurial intention (Lee, 2021). Furthermore, existing studies have identified job stress and job dissatisfaction as the dominant job-related negative factors, while entrepreneurial opportunities and expected benefits are the main entrepreneurial-related pull factors that attract academics to engage in academic entrepreneurship (Gambardella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%